Pro-Inflammatory and Pro-Oxidative Changes During Nilotinib Treatment in CML Patients: Results of a Prospective Multicenter Front-Line TKIs Study (KIARO Study) - Sicuranza, Anna; Ferrigno, Ilaria; Abruzzese, Elisabetta; Iurlo, Alessandra; Galimberti, Sara; Gozzini, Antonella; Luciano, Luigiana; Stagno, Fabio; Russo Rossi, Antonella; Sgherza, Nicola; Cattaneo, Daniele; Zuanelli Brambilla, Corrado; et al. (Frontiers in Oncology, 2022)
Tyrosine kinase inhibitors (TKI) may offer a normal life expectancy to Chronic Myeloid Leukemia (CML) patients. However, during treatment with nilotinib, a higher than expected incidence of arterial occlusive events (AOEs) was observed. We previously showed an “inflammatory status” during nilotinib that may explain increased incidence of AOEs. Thus, we conducted this prospective KIARO study including 186 CML patients (89 imatinib, 59 nilotinib, 38 dasatinib). Interleukin 6 (IL6), interleukin 10 (IL10), Tumor Necrosis Factor-α (TNFα), oxLDL and high-sensitivity C-reactive protein (hs-CRP) plasma levels were measured at diagnosis and during treatment, with the aim to investigate changes in each patient’s inflammatory status favoring AOEs. Clinical and biochemical pro-atherothrombotic profiles and the 10-year SCORE chart were also evaluated. We showed a pro-inflammatory/pro-oxidative milieu increasing along treatment with nilotinib compared with imatinib or dasatinib, as demonstrated by higher hs-CRP and oxLDL levels and increased IL6/IL10 and TNFα/IL10 ratios only in nilotinib cohort. After median follow-up of 23.3 months from TKI start, 10/186 patients (5.4%) suffered an AOE. 5/10 (50%) AOEs occurred during nilotinib treatment despite a lower 10-year SCORE and a lower median age in this subgroup. A longer follow-up is needed to further confirm the active role of nilotinib in AOEs pathogenesis.